UKRAINE’S ENERGY POLICY IN THE POST-SOVIET ERA - Y. V. Borovsky (Vestnik MGIMO-Universiteta)
Following the collapse of the USSR, Ukraine has found itself in a heavy, almost insurmountable dependence on imported oil and gas resources. However, owing to the inherited soviet infrastructure and strategic location, it has become a key transit state, capable of controlling the main flows of hydrocarbons from Russia to Europe. Due to these circumstances, a deep, politically motivated and often irreconcilable competition in the triangle Ukraine-Russia and the West has emerged. In the post-Soviet era the Ukrainian authorities, irrespective of their political affiliations, have tried to diversify the Russian oil and gas supplies either by securing deliveries from other sources or by enhancing production within the country. Opposing any Russian initiative aimed at diminishing the transit status of Ukraine (for example, Nord Stream-1,2, South Stream, etc.), Kiev has struggled to keep Ukraine's gas transportation system under the national control. In addition to this, many western energy companies have got invitation from Ukraine to start exploration and production operations in the country. Such a behavior of the Ukrainian leadership, incompatible to a large extent with the Russia interests, was unanimously supported by Washington and Brussels in the 1990s and afterwards. Ukraine, initially involved in the multilateral energy cooperation with the Russian participation, decided to change its camp and join the pro-Western international energy institutions: GUAM, the Energy Charter Treaty and the Energy community. With the backing of Washington and Brussels, Kiev initiated two projects (the Eurasian Oil Transport Corridor, White Stream) designed to secure oil and gas supplies from the Caspian region to Europe bypassing Russia.